Subtraction of the t t ¯ $$ t\overline{t} $$ contribution in tW b ¯ $$ tW\overline{b} $$ production at the one-loop level - Liang Dong; Hai Tao Li; Zheng-Yu Li; Jian Wang (Journal of High Energy Physics)
Abstract The tW b ¯ $$ tW\overline{b} $$ production contributes to the real corrections to the tW cross section. It would interfere with the top quark pair production, causing difficulties in a clear definition of the tW b ¯ $$ tW\overline{b} $$ events. The subtraction of the t t ¯ $$ t\overline{t} $$ contributions has been performed in the diagram removal or diagram subtraction schemes for the tree-level processes. However, these schemes rely on the ability to identify the double resonant diagrams and thus can not be extended to loop diagrams. We propose a new scheme to subtract the t t ¯ $$ t\overline{t} $$ contributions by power expansion of the squared amplitude in the resonant region. In order to cancel the infra-red divergences of the loop amplitudes, a widely used method is to introduce the dipole counter-terms, an ingredient in calculations of the full next-to-leading order QCD corrections. In our scheme, these counter-terms are also power-expanded. As a proof of principle, we calculate the one-loop correction to the d d ¯ $$ d\overline{d} $$ → b ¯ Wt $$ \overline{b} Wt $$ process, and present the invariant mass distribution of the W b ¯ $$ W\overline{b} $$ system.